Incidental findings in neuroimaging and their management a guide for radiologists, neurosurgeons, and neurologists - Westmark, Kaye D.; Kim, Dong H.; Riascos, Roy (Thieme, 2020)
"Incidental Findings in Neuroimaging and Their Management: A Guide for Radiologists, Neurosurgeons, and Neurologists presents a streamlined, case-based approach to 50 commonly seen incidental findings in neuroimaging. Edited by Kaye D. Westmark, Dong H. Kim, and Roy F. Riascos, this unique book provides the necessary knowledge to manage significant unexpected findings-from identification and analysis to efficacious interventions. With collaborative contributions from neuroradiologists, neurosurgeons, neurologists, otolaryngologists, body and musculoskeletal imaging experts, endocrinologists, and hematologists/oncologists, this resource encompasses a wide spectrum of incidental findings. Organized into six sections, the book starts with normal variants that are extremely important to recognize in order to avoid unwarranted additional testing and unnecessary stress for the patient. Subsequent sections detail abnormalities that require extensive clinical evaluation in order to determine ideal management. These include incidental findings for extracranial, extraspinal, intracranial, and intraspinal imaging. The final section outlines CT and MR imaging artifacts that are particularly concerning because they may mimic more dangerous pathologies while degrading imaging quality and obscuring real findings. Key Features Key findings and differential diagnosis are listed for each entity Diagnostic decision trees present algorithms in an easy-to-understand manner Artifact analyses explain the technical reason for each artifact and what can be done to mitigate effects Clinical Q & As connect the radiologic diagnosis with actual case management decisions and provide in-depth background information that is applicable to management in various scenarios This essential guide will help trainee and practicing neuroradiologists, neurosurgeons, and neurologists interpret incidental spine and brain imaging findings and make clinically informed, complex treatment decisions"--